The non-shock of PIAAC – Tracing the discursive effects of PIAAC in Denmark. (November 2015) - Cort, Pia; Larson, Anne
The results of the first PIAAC survey were published in October 2013. In the case of Denmark, the survey showed that Denmark is below the OECD average when it comes to reading skills, above average with regards to numeracy and on average with regards to IT skills. In this paper we analyse how the PIAAC results were covered by the media and how different stakeholders within the field of adult literacy took PIAAC as an opportunity to try to influence how the problem of adult literacy in Denmark should be represented. The analysis is based on Bacchi's What's the problem represented to be? approach to policy analysis (2009) and Kingdon (1984), and Zahariadis' (2003) multiple streams theory. The analysis shows that PIAAC did not provoke the same kind of national 'shock' as PISA and that adult literacy is low on the political agenda compared to basic schooling.